Online programs build confidence and improve healthy eating messages in Early Years services. Issue 2 (June 2019) - Devine, Amanda; Wallace, Ruth; Lo, Johnny; Miller, Margaret; Sambell, Ros; Costello, Leesa; Lombardi, Karen; Veurink, Samantha
Building on the success of the SNAC (Supporting Nutrition Australian Childcare) community, a comprehensive online programme SNAC Plus provided professional development (PD) and resources to embed nutrition curriculum and supportive food environments in Early Childhood Education and Care (ECEC) services. Process and impact evaluation were conducted to determine the effectiveness of this intervention programme. Participants were recruited from nine long-day-care (LDC) centres and the current SNAC membership list. Resource access was monitored using web analytics. Changes in nutrition knowledge, attitudes, behaviours and food environment were measured using baseline (comparator group, n =100) and post-intervention surveys (intervention group, n =80), contextualised through open-ended questions. The majority of comparator participants perceived nutritious food provision as important yet lacked confidence about estimating serve sizes. Adjusting for years of experience, the intervention significantly influenced educators' confidence about servings of grains ( p =0.034), dairy ( p =0.015), low fat meat ( p =0.014) and food group servings estimation knowledge ( p <0.001). Intervention participants accessed credible websites and health professionals for nutrition knowledge; reported SNAC Plus positively influenced changes to food service and role-modelling; and knowledge, attitudes and behaviours improved at organisational and individual levels. SNAC Plus provides online nutrition curriculum resources that positively impacted knowledge, attitudes and behaviours of ECEC staff and influenced systematic changes in food environments. Practice and policy implementation that includes all systems within the early years setting will help initiate and maintain healthy food environments.